Simulation of Decoherence by Averaged Semiquantum Method (Communications in Computational Physics, 2010)
We investigate the dynamics of a system coupled to an environment by averagedsemiquantum method. The theory origins from the time-dependent variationalprinciple (TDVP) formulation and contains nondiagonal matrix elements, thus it canbe applied to study dissipation, measurement and decoherence problems in the model.In the calculation, the influence of the environment governed by differential dynamicalequation is incorporated using a mean field. We have performed averaged semiquantummethod for a spin-boson model, which reproduces the results from stochasticSchrodinger equation method and Hierarchical approach quite accurately. Moreover,we validate our results with noninteracting-blip approximation (NIBA) and generalizedSmoluchowski equation (GSE). The problem dynamics in nonequilibrium environmentshas also been studied by our method. When applied to the harmonic oscillatormodel coupled to a heat bath with different coupling strengths and dimensionalitiesof the bath, we find that the loss of coherence predicted by semiquantum methodis identical to the result of master equation with different initial state (Gaussian wavepacket and superposed wave packets).